Lake-Level Oscillation Based on Sediment Strata and Geochemical Proxies Since 11,000 Year From Tengger Nuur, Inner Mongolia, China - Chengjun, Zhang; Li, Zhang; Wanyi, Zhang; Yunhan, Tao; Yang, Liu; Xiangling, Wan; Zhen, Zhang; Khomid, Safarov (Frontiers in Earth Science, 2020)
A 794-cm section was collected from Tengger Nuur in the Inner Mongolian Plateau. Accelerator mass spectrometry 14C data were determined to set an age-depth model after removing about 1920 years of the carbon reservoir effect. Based on the multi-proxies grain size, carbonate-content, total organic carbon-content, ratio of C/N, ratios of Mg/Ca and Sr/Ca, and carbonate carbon and oxygen isotopes, paleoenvironmental changes since the last deglaciation were reconstructed. Tengger Nuur was very shallow during the last deglaciation under a cool and wet climate, especially during the interval of the cold Younger Dryas event. Although, temperature and humidity increased from the early Holocene (∼10,450–8750 cal a BP), low lake levels indicated that the summer monsoon was not sufficiently strong to reach the modern monsoon boundary in Inner Mongolia. High monsoon precipitation caused lake expansion during 8750–5000 cal a BP, but the lake level oscillated in a shallow state under high evaporation. A low lake-level event occurred with the interval of a cold-wet climate during 5450–5100 cal a BP. The summer monsoon receded gradually to maintain a deep lake under high effective humidity during 5000–2000 cal a BP, punctuated by low lake-level events at intervals of 4300–3980 cal a BP and 3700–2750 cal a BP. With the arrival of the cold and dry westerly after 2000 cal a BP, lakes shrank gradually to become salinized or completely desiccated, but their levels oscillated at shallow depths during the four periods of 1900–1800 cal a BP, 1500–1050 cal a BP, 550–400 cal a BP (Little Ice Age), and 100 cal a BP–AD 1985. Therefore, the eastern summer monsoon was weak in the early Holocene, and lake-level oscillation was controlled by effective humidity in arid and semi-arid areas.